An Integrated Model for Health Insurance Fund Consolidation with Emphasis on the Experiences of Selected Countries - Dehghanpour, Babak; Etebarian Khorasgani, Akbar; Aghadavood, Seyed Rasoul; Shahnoushi Forushani, Mojtaba (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The primary objective of this study is to develop an operational model for the integration of health insurance funds with a comparative approach, focusing on the experiences of Japan, Singapore, Turkey, Sweden, Norway, China, and Iran. Methodology: This research utilizes a mixed-method approach (sequential exploratory) involving both qualitative and quantitative analyses. The qualitative phase involved a review of literature and expert interviews, which identified key indicators from the selected countries. In the quantitative phase, these indicators were tested using structural equation modeling (SEM) to quantify the proposed model. Data were collected from a sample of 20 experts through interviews, and the model’s fit was assessed using various fit indices. Findings: The study identified seven key dimensions that influence the integration of health insurance systems: structural factors, behavioral factors, environmental factors, processes, outcomes, and their respective subcomponents. The analysis revealed that these dimensions collectively explain approximately 89% of the variance in health insurance integration. The proposed model demonstrated a good fit with the empirical data, confirming the significance of the identified factors. Conclusion: The findings suggest that the proposed model, which includes structural, behavioral, environmental, and process factors, is effective in guiding the integration of health insurance funds. The study recommends implementing policies that reduce management levels, enhance stakeholder cooperation, and continuously improve service delivery processes. The model provides a robust framework for improving the integration of health insurance services in Iran and could be adapted for use in other developing countries facing similar challenges. Further research is recommended to explore additional dimensions and apply the model in different contexts.